2014
DOI: 10.1142/s0217979214501434
|View full text |Cite
|
Sign up to set email alerts
|

Stripe phases in a frustrated spin-1/2 dimer Heisenberg model

Abstract: We use a bond-operator mean-field theory and a generalized spin-wave theory to study the frustrated spin-1/2 dimer Heisenberg model on a square lattice with frustrations in both cardinal and corner directions. We establish the ground state phase diagram with very rich phases. It has been disclosed that the frustrations in cardinal directions can induce exotic superfluid (SF) and supersolid (SS) phases. By introducing the frustrations in corner directions, we found more interesting phases, such as the striped s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Combination of these two apparently antithetical properties has attracted the attentions of both experimentalists and theorists, and searching for this phase has become one of the main subjects of condensed matter and cold atoms physics [5,6,7,8,9,10,11,12]. An appropriate ground for searching various supersolid phases are quantum spin systems [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. Recently it has been shown experimentally that mixed-spin systems, composed of two kinds of spin, display various supersolid phases in their ground state phase diagrams [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Combination of these two apparently antithetical properties has attracted the attentions of both experimentalists and theorists, and searching for this phase has become one of the main subjects of condensed matter and cold atoms physics [5,6,7,8,9,10,11,12]. An appropriate ground for searching various supersolid phases are quantum spin systems [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. Recently it has been shown experimentally that mixed-spin systems, composed of two kinds of spin, display various supersolid phases in their ground state phase diagrams [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Another appropriate ground for searching various supersolid phases are quantum spin systems. It has been shown that 1D spin-1 chains [41,42,43], 2D frustrated spin-1/2 [44,45,46,47,48,49,50,51,52,53,54,55] and spin-1 [56,57,58,59] models in an external magnetic field and 3D spin models [60,61] possess different kinds of stripe, checkerboard and star supersolid phases. However, in spite of many studies on uniform spin systems, the supersolidity of mixed-spin systems has not been addressed so far.…”
Section: Introductionmentioning
confidence: 99%